Squamos Odontogenic Tumor: A case report - Paolo De Angelis; Camilla Cavalcanti; Giuseppe De Rosa; Noemi Cesaroni; Teresa Musarra; Antonio D'Addona (Publymed, 2023)
A 40-year-old male patient presented with diffuse radiolucent lesions on the upper maxilla at the apex of the incisors, canines, premolars, and molars. Surgical excision of the lesions was performed, and the biopsy specimens were submitted for histological analysis: the lesions of the first quadrant were found to be a squamous odontogenic tumor, a rare benign neoplasm of odontogenic origin. The purpose of this article is to describe the clinical, radiographic and histological aspects of odontogenic squamous tumor.